Water Purification using Graphene Covered Micro-porous, Reusable Carbon Membrane. Issue 20 (15th March 2016) - Pawar, Pranav Bhagwan; Maurya, Santosh K; Chaudhary, Ragvendra Pratap; Badhe, Dhanashree; Saxena, Sumit; Shukla, Shobha
ABSTRACT: The discovery of graphene based materials has led to significant advancement in several different areas. The large surface area, nanoporous structure and availability of delocalized electron network provide a unique opportunity for purification of solvents via adsorption, absorption or simple trapping. This makes graphene based materials as potential candidates for purification and desalination of water. Here we report synthesis of 3D porous network of oxidized graphene for purification of sea water. The membranes fabricated using these frameworks are hierarchically linked intrinsically defected oxidised graphene sheets by long micro-channels and capable of filtering small ions such as Na + and Cl - . These are easy to fabricate, reusable and economically viable especially for point of use application. We finally show a fabricated device using membrane made from these 3D networks of oxidized graphene.